VIDEO-ASSISTED THORACIC SURGERY USING LOCAL ANESTHESIA IN LUNG ABSCESSES AND PYOPNEUMOTHORAX - A. L. Akopov; V. I. Egorov; I. V. Deinega; P. M. Ionov (Вестник хирургии имени И.И. Грекова)
The article presents the results of 42 video-abscessoscopies (VAS) in acute and gangrenous lung abscess and 32 video-thoracoscopies (VTS) in pyopneumothorax, which were performed using local anesthesia and sedation. There were several indication to operation: sanation of cavities, removal of necrotic sequestration and fibrin, decollement, biopsy. Perioperative complications developed after 11 surgeries (13%): emphysema of soft tissues of pectoral cells (5), phlegmon of the thorax (3), bronchial hemorrhage (2), pneumothorax (1). One of the patients died, because of progressing of main disease. VAS and VTS were carried out in 5-8 days after cavity drainage of abscess or pleural cavity in 50 patients. In other 15 cases operations were performed directly before drainage. The bronchial hemorrhage and phlegmons of the thorax were noted in patients of second group. The patients had good tolerance of VAS and VTS operations fulfilled using local anesthesia and sedation. They are safe in case that operation follows drainage of abscess or pleural cavity after decrease of inflammatory processes.